Review of Genus Zyginella Löw (Hemiptera: Cicadellidae: Typhlocybinae: Zyginellini) with Description of Four New Species and a New Genus from China - Zhang, Yalin; Gao, Xia; Huang, Min (Zootaxa, 2012)
Species in the genus Zyginella Löw from China are reviewed and four new species, Zyginella petala, Z. processa, Z. dwor-akowskae and Z. sichuanensis spp. nov. are described and illustrated. A key to nine species of Zyginella from China isprovided along with a world species checklist. Parathailocyba gen. nov. (type species Parathailocyba orla (Dworakowska, 1977) comb. nov., transferred from Zyginella Löw) is also described and illustrated.